Biophysics : Principles And Techniques. - M A Subramanian (MJP Publishers, 2005)
Biophysics deals with the role of physical principles in the organization and functioning of living systems. This book narrates the interrelationship among the physical principles, chemical composition and biology of living organisms. The principles and techniques of biophysics are systematically dealt with, making the contents easy to assimilate. The up-to-date techniques in the field of biophysics are comprehensively covered